2001
DOI: 10.1034/j.1600-0773.2001.d01-101.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Mechanism of 2-Chloro-3-(4-hexylphenyl)-amino-1,4-naphthoquinone (NQ304), an Antithrombotic Agent

Abstract: The effects of 2-chloro-3-(4-hexylphenyl)-amino-1,4-naphthoquinone (NQ304), an antithrombotic agent, on aggregation, binding of fibrinogen to glycoprotein IIb/IIIa and intracellular signals were investigated using human platelets. NQ304 inhibited thrombin-, arachidonic acid- and thapsigargin-induced aggregation of washed human platelets with the IC50 values of 22.2+/-0.7, 6.5+/-0.2, and 7.6+/-0.1 microM, respectively. NQ304 significantly inhibited fluorescein isothiocyanate-conjugated fibrinogen binding to hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It has been reported that several compounds with the backbone of 1,4-naphthoquinone chemical structure possess antiplatelet activities [13][14][15][16]. We have also previously reported that some 1,4-naphthoquinone derivatives possessed antiplatelet and antithrombotic effects [17][18][19][20][21]. These results indicate that this congener compound may be a new source in the antiplatelet and antithrombotic drug development.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…It has been reported that several compounds with the backbone of 1,4-naphthoquinone chemical structure possess antiplatelet activities [13][14][15][16]. We have also previously reported that some 1,4-naphthoquinone derivatives possessed antiplatelet and antithrombotic effects [17][18][19][20][21]. These results indicate that this congener compound may be a new source in the antiplatelet and antithrombotic drug development.…”
Section: Introductionmentioning
confidence: 68%
“…It has been reported that NTP, a synthesized 1,4-naphthoquinone derivative, inhibited platelet aggregation by decreasing [Ca 2+ ] i elevation [16]. In our previous studies, some 1,4-naphthoquinone derivatives also inhibited platelet aggregation by inhibition of Ca 2+ mobilization [20,21]. Thus, it was not unreasonable to hypothesize that the antiplatelet activities of J78 may partly relate to its inhibition of Ca 2+ mobilization at least.…”
Section: Inhibitory Effects Of J78 On Experimental Thrombosis and Plamentioning
confidence: 93%
See 1 more Smart Citation